Implementasi pembelajaran investigasi berbantuan Software Cabri 3D terhadap kemampuan pemecahan masalah matematis dan kemandirian belajar mahasiswa - Ike Natalliasari; Eva Mulyani (JP3M (Jurnal Penelitian Pendidikan dan Pengajaran Matematika), 2017)
This study aims to determine the effect of the application of instructional investigation-assisted Cabri 3D software to students’ mathematical problem-solving abilities, knowing the difference of mathematical problem solving ability among students who received instructional investigation with the help of Cabri 3D software with those who obtained conventional learning seen from high, low and describe the independence of student learning on the application of investigative learning assisted Cabri 3D software. The method used in this research is the descriptive quantitative method. The population in this study is all students of Mathematics Education Department of Siliwangi University class of 2015/2016, while the sample in this research is the students who take the subjects of Kapita Selekta Matematika SMA II as much as two classes. The first class consisted of 30 students, used as an experimental group using instructional investigation assisted by Cabri 3D software and second class consist of 31 students, used as the control group with learning using conventional learning. Based on the research results, it can be concluded that (1) There is a positive influence of the application of investigative learning with the help of Cabri 3D software to the students’ mathematical problem-solving abilities. The outcome target of this research is scientific publication published in the national journal having ISSN and proceeding at the national seminar on mathematics education.